Comprehensive Analysis Of Bhabinkamtibmas Involvement In The Framework Of Conducive Elections With Integrity - Neilpon Yulinar Marquez; Tri Sosilowati (Universitas Sains dan Teknologi Komputer, 2023)
Bhabinkamtibmas is one of the figures in the Indonesian National Police (POLRI) institution that is closest to the community, because it has a small work area at the sub-district or village level. This closeness can then be used as a means of education as well as socialization, regarding how to make elections conducive and with integrity. This condition is a situation that needs to be realized, in order to build public trust and also maintain societal stability. This research was carried out using normative legal research and a sociological approach, which was then analyzed using qualitative methods. The results of this research are that Bhabinkamtibmas can be used as part of an effort to construct elections that are conducive and have integrity through a social-based system approach.